5-Hydroxy-7-azaindolin-2-one, a novel hybrid of pyridinol and sunitinib: design, synthesis and cytotoxicity against cancer cells. Issue 21 (5th May 2016) - Shah, Sajita; Lee, Chaemin; Choi, Hyukjae; Gautam, Jaya; Jang, Hyeonjin; Kim, Geum Jin; Lee, Yu-Jeong; Chaudhary, Chhabi Lal; Park, Sang Won; Nam, Tae-gyu; Kim, Jung-Ae; Jeong, Byeong-Seon
Abstract : Synthesis of a series of hybrid compounds of pyridinol and sunitinib and their cytotoxicity against human cancer cell lines and improved safety windows are described. Abstract : Angiogenesis plays important roles in tumor growth and metastasis. Sunitinib (Sutent®) is an antitumor agent targeting receptor tyrosine kinases which are involved in angiogenesis as well as cancer cell growth and survival. Using the pyridin-3-ol scaffold, which was previously reported as an excellent antioxidant and antiangiogenic platform, we have synthesized sunitinib mimics6 by hybridizing bicyclic pyridinol4 as a key scaffold and pyrrole-2-carbaldehydes7 as side chains. Cytotoxicity assays showed that compounds6 have comparable to better anticancer activity than sunitinib against five different cancer cell lines. In addition, compounds6 showed even lower levels of cytotoxicity against normal cells, resulting in up to 26-fold better safety windows, than sunitinib. Signaling pathway-associated transcription factor reporter assay and western blot analyses revealed that apoptosis induction in MDA-MB-231 human breast cancer cells by6F is mainly mediated through the p53 increase and down-regulation of phospho-signal transducer and activator of transcription 3 (STAT3) and its target gene products, cyclin D, Bcl-2, and survivin. The data strongly suggest that our hybrid compounds can provide a novel anticancer scaffold with improved and safer cytotoxicity profiles than sunitinib.